Traditional hierarchies and affirmative action in a globalizing economy: evidence from India - Deshpande, Ashwini; Ramachandran, Rajesh (World development, 2019)
We compare successive age cohorts of three broad social groups - Scheduled Castes and Tribes (SC-STs), Other Backward Classes (OBCs) and “Others” and provide the first disaggregated picture of the evolution of inter-caste disparities in India. The results show that absolute caste gaps in years of schooling and prestigious occupation of white-collar jobs have remained static, whereas log wages below the median have convergence and above the median diverged. Examining extension of job quotas to OBCs in 1993, we find positive effects of affirmative action on probability of holding government jobs, as well as on secondary schooling completion.
Gesehen am 09.05.2019
Keywords: Indien